Finding a Home: Stopping Theory and Its Application to Home Range Establishment in a Novel Environment - Saltz, David; Getz, Wayne M. (Frontiers in Conservation Science, 2021)
Familiarity with the landscape increases foraging efficiency and safety. Thus, when animals are confronted with a novel environment, either by natural dispersal or translocation, establishing a home range becomes a priority. However, while the search for a home range caries a cost of functioning in an unfamiliar environment, ceasing the search carries a cost of missed opportunities. The process is predominantly heuristic, where the animal must decide how to study the environment and, consequently, when to stop searching and establish a home range in a manner that will reduce the cost and maximize or at least satisfice its fitness. These issues fall within the framework of stopping theory. In this paper we review stopping theory and three stopping rules relevant to home range establishment: the best-of-n rule, the threshold rule, and the comparative Bayes rule. We then hypothesize when each rule should be practiced, and what and how environmental factors and animal attributes are expected to affect the stopping time. We provide a set of stopping-theory-related predictions that are testable within the context of translocation projects.